Predictors of change in global psychiatric functioning at an inpatient adolescent psychiatric unit: A decade of experience. (April 2020) - Kennedy, Jane; Hembry, Philippa; Green, Dan; Skuse, David; Lewis, Simon
Background: Psychiatric inpatient treatment for children is sometimes beneficial, but predictors of who benefits, and in what circumstances, are largely unknown. This study aimed to identify personal and environmental factors that influence outcome in an adolescent unit that accepts both emergency and planned admissions. Methods: Routine standardised intake and outcome measures were analysed for the period 2009–2018. Potential predictors assessed included the Children's Global Assessment Scale (CGAS), engagement with treatment, behavioural attitudes and peer relationships on the unit. Findings: One hundred and twelve admissions were tracked. Mean age of admission was 16 years, and 71% were female. A total of 61% had higher (better) CGAS scores on discharge than on admission; 34% of inpatients fully engaged with their treatment. Median admission duration was 118 days for males and 196 days for females. Admission lengths were much shorter for ethnic minority patients, but group sizes were small. Longer admissions led to greater improvement. Poor outcomes were associated with failure to engage with treatment and a deterioration in peer relationships. Interpretation: Compliance with treatment and female gender were both significant predictors of positive change during admission. The establishment of good and supportive peer relationships during the admission was also a potent indicator of benefit.